Cinnamtannin B-1, a novel antioxidant for sperm in red deer - Sánchez-Rubio, F; Fernández-Santos, M R; Castro-Vázquez, L; García-Álvarez, O; Maroto-Morales, A; Soler, A J; Martínez-Pastor, F; Garde, J J (Animal reproduction science, 2018)
Cinnamtannin B-1 (CNB-1) is a naturally occurring trimeric A-type proanthocyanidin contained in several plants such as cinnamon (Cinnamomum zeylanicum). It is considered to be a potent antioxidant. The protective effect of CNB-1 against oxidative stress was assessed in red deer epididymal sperm incubated at 37 °C. Cryopreserved sperm from six stags were thawed, pooled and extended to 400 × 106 sperm/ml in BGM (bovine gamete medium). After being aliquoted, the samples were supplemented with different concentrations of CNB-1 (0, 0.1, 1, 10 and 100 μg/mL), with or without induced oxidative stress (100 μM Fe2+/ascorbate). The samples were evaluated after 0, 2 and 4 h of incubation at 37 °C. This experiment was replicated six times. Spermmotility (CASA), viability, mitochondrial membrane potential, acrosomal status, lipoperoxidation (C11 BODIPY 581/591), intracellular reactive oxygen species (ROS) production and DNA status (TUNEL) were assessed. After 4 h of incubation, CNB-1 prevented the deleterious effects of oxidative stress, thus improved sperm progressivity and velocity (P<0.05). Furthermore, 1 and 10 μM CNB-1 improved sperm linearity, even when compared to those samples that had not been subjected to oxidative stress (P<0.05). The greatest concentration, 100 μM, prevented sperm lipoperoxidation and reduced ROS production in samples subjected to oxidative stress.
Keywords: Cell Survival; Oxidative Stress; Antioxidant; reaktivní formy kyslíku; Deer; vysoká zvěř; oxidační stres; spermie; Deer-; Sperm Motility; viabilita buněk; peroxidace lipidů; Proanthocyanidins; Cinnamtannin B-1; Antioxidants; zvířata; Reactive Oxygen Species; fragmentace DNA; Sperm oxidative stress; antioxidancia; motilita spermií; Male; Semen Preservation; DNA Fragmentation; uchování spermatu; Spermatozoa; Animals; mužské pohlaví; proantokyanidiny; Lipid Peroxidation